2008
DOI: 10.1002/ejoc.200800552
|View full text |Cite
|
Sign up to set email alerts
|

Zn Pyropheophorbide a: A β‐Face Selective Nicotine Receptor

Abstract: Nicotine binds to a semisynthetic chlorophyll a derivative, Zn pyropheophorbide a, in a receptor‐like manner to form a 1:1 complex with β‐face diastereomeric configuration. The geometry of the complex structure was evidenced by 1H NMR, ROESY and DOSY spectroscopic experiments combined with molecular modelling DFT B3LYP calculations at the 6‐31G* level. The observed binding between the chlorin and nicotine takes place through a “two‐point binding” mechanism, in which the nicotine N‐pyridyl moiety coordinates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Chlorophyll a was extracted and puried from Spirulina pacica and converted into pyro-pheophorbide a methylester (1), 33 which was used as a starting material for the syntheses. Zn pyropheophorbide a methylester 24,25 and Zn 3 1 -OH-pyro-pheophorbide a methylester (3 1 -epimeric mixture, (3 1 R)/(3 1 S) ¼ 1/1) 34 ( Fig. 2) were synthesized according to literature procedures and their NMR spectra were in agreement with the published data.…”
Section: Synthesissupporting
confidence: 58%
“…Chlorophyll a was extracted and puried from Spirulina pacica and converted into pyro-pheophorbide a methylester (1), 33 which was used as a starting material for the syntheses. Zn pyropheophorbide a methylester 24,25 and Zn 3 1 -OH-pyro-pheophorbide a methylester (3 1 -epimeric mixture, (3 1 R)/(3 1 S) ¼ 1/1) 34 ( Fig. 2) were synthesized according to literature procedures and their NMR spectra were in agreement with the published data.…”
Section: Synthesissupporting
confidence: 58%
“…These peaks coalesced with an increasei nt emperature and relatively sharp peaks wereo btained at 373 K, showing the monomeric specieso fZn-1.T he signals of 5-H and 3 1 -N(CH 3 ) 2 shifted to higher magneticf ields upon cooling to 223 K. These large shifts were ascribable to the shielding effect of the ring current of the chlorin p-system, where their protons were situated above the chlorin moiety via axial coordination of the 3 1 -N atom to the central zinc. [26][27][28][29] Since the shift values of 10-H and 20-H were smaller ( Figure 7, blue square), at low temperature, they were located at relativelyd istant positions from the other chlorin moiety in the resulting supramolecule. When considering the combination of 1 HNMR data with the above optical observations, Zn-1 (1 mm)w as monomeric in CDCl 2 CDCl 2 at 373 K, forminga no pen dimer with af lexible conformationa t room temperature, and transforming to closed dimers which take various conformers through double coordinate bonds with restriction of molecular motion at low temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…Due to the fact that RM1 has not been parameterized for transition metals, only few articles have used RM1 in the context of inorganic chemistry. [155][156][157][158][159] RM1 was mostly restricted to the calculation of properties of the ligands that are interacting with metals 158 and to the calculation of the properties of the inorganic species that participate in organic reactions. 140 Examples of the usage of RM1 in inorganic chemistry include a study of the CO 2 absorption by protic and aprotic ionic liquids, 157 as well as the prediction of HOMO, and LUMO energies of ligands coordinated to trivalent dysprosium and geometry optimization of a set of ligands coordinated to trivalent europium, ytterbium and holmium.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…Inorganic chemistry studies also reported the usage of RM1 as the first step in higher accuracy geometry optimization calculations. 158,159 This strategy can result in a much more adequate starting geometry to more accurate calculations that will employ DFT or ab initio methods. For example, Kavakka et al 158 reported a zinc complex, which is a selective nicotine receptor.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
See 1 more Smart Citation